Response of Leucaena to inoculation compared under different fertilizer treatments - Valarini, Maria José; Bufarah, Gilberto (Pesquisa Agropecuaria Brasileira, 2014)
The tree legume Leucaena leucocephala (Lam.) de Witt., has a great potential for utilization in tropical agriculture, particularly in animal nutrition as an alternative protein source during dry periods, and in enriching the soil, both uses relying on its capacity for nitrogen fixation. With the aim of evaluating symbiotic nitrogen fixation in Leucaena an experiment was performed at the Instituto de Zootecnia, Nova Odessa, São Paulo, in cooperation with and following the experimental guidelines of the Niftal Project. The field trial was designed to test the effect of fertilization (lime + single super phosphate + KCl) and sources of nitrogen (inoculation, urea and control) in a 2 x 3 factorial design. The total nitrogen and dry matter production in kg.ha-1 –year-1 at the first cut were respectively: 106 ± 14 and 2416 ± 335, for fertilization + inoculation; 80 ± 14 and 1906 ± 316, for fertilization + urea; 70 ± 8 and 1798 ± 249, for fertilization; 67 ± 10 and 1902 ± 359, for inoculation; 29 ± 8 and 754 ± 193, for urea; and 50 ± 10 and 1039 ± 247 for the control. The statistical analysis showed significant responses to fertilization and/or inoculation, this latter being the best source of nitrogen in the experiment. The treatment with urea alone was the worst of all, suggesting the occurrence of acidification, which not only adversely affected the micro but also the macrosymbiont.